Explaining the relationship between the third moderate movement and the new middle class in Iran after the Islamic Revolution. - Amir Hemati; Abas Hatami; Ali Alihosaini; Hamid Nasaj (رهیافتهای سیاسی و بین المللی)
This article uses the concept of explanation in the "critical discourse analysis" method of Norman Farclough, in order to explain the two-way relationship between the six elements of the third middle class and the new middle class (urban) in the post-Islamic revolution period It is Iran. In this direction, first, a general picture of the six elements of the aforementioned flow will be drawn, and then the relationship between these elements and the new middle class will be analyzed. The main question is whether the relationship between this flow and that class is normative (reproduction) or creative (attempt to change)? Surveys show that this relationship has been normative and creative at the same time; That is, on the one hand, the third moderate current can be considered as a part of the class struggle of the new middle class, and on the other hand, this current has the capacity to represent all the demands of that class and seeks to create changes in It has been. The new middle class has also been one of the variables influencing the emergence and changes of the discourse of this current and has been able to make the discourse of the said current closer to its ideals.